Faktor-Faktor yang Mempengaruhi Pengetahuan Ibu tentang Kejang pada Balita - Jumiyati, Jumiyati; Riana, Hernah; Afni, Nur (Department of Pharmacy, Bumigora University, 2024)
Febrile seizures are the most common neurological disorder in children, with 1 in 25 children having one febrile seizure. Febrile convulsions are seizures that occur when the body temperature rises (rectal temperature over 38°C) due to an extracranial process. Febrile seizures can result in behavioral disturbances as well as decreased intelligence and academic achievement. According to the World Health Organization (WHO), it is estimated that the number of children who experience febrile seizures in the world is more than 21.65 million and more than 216 thousand children die. Therefore, it is important that mothers know about seizures. This study aims to determine the factors that influence maternal knowledge about seizures based on age, parity and maternal education. This research is an analytic survey with a cross sectional approach. This study was conducted in the working area of Puskesmas Kolaka. The research sample was 82 respondents where the instrument used was a questionnaire. The results of the study there is an influence between age and maternal knowledge about seizures p=0.015, parity with maternal knowledge about seizures p=0.003, education with maternal knowledge about seizures p=0.025. Conclusion. there is an influence between age, parity and maternal education about seizures. Suggestions to improve mothers' knowledge about seizures by providing education and promotion about handling toddlers who experience febrile seizures.